Reproducibility of cine displacement encoding with stimulated echoes (DENSE) in human subjects - Lin, Kai; Meng, Leng; Collins, Jeremy D.; Chowdhary, Varun; Markl, Michael; Carr, James C. (Magnetic resonance imaging, 2017)
To test the hypothesis that two-dimensional (2D) displacement encoding via stimulated echoes (DENSE) is a reproducible technique for the depiction of segmental myocardial motion in human subjects. Following the approval of the institutional review board (IRB), 17 healthy volunteers without documented history of cardiovascular disease were recruited. For each participant, 2D DENSE were performed twice (at different days) and the images were obtained at basal, midventricular and apical levels of the left ventricle (LV) with a short-axis view. The radial thickening strain (Err), circumferential strain (Ecc), twist and torsion were calculated. The intra-, inter-observer and inter-study variations of DENSE-derived myocardial motion indices were evaluated using coefficient of variation (CoV) and intra-class correlation coefficient (ICC). In total, there are 272 pairs of myocardial segments (data points) for comparison. There is good intra- and inter-observer reproducibility for all DENSE-derived measures in 17 participants. There is good inter-study reproducibility for peak Ecc (CoV=19.64%, ICC=0.8896, p<0.001), twist (CoV=33.11%, ICC=0.9135, p<0.001) and torsion (CoV=13.96%, ICC=0.8684, p<0.001). There is moderate inter-study reproducibility for Err (CoV=38.89%, ICC=0.7022, p<0.001). DENSE is a reproducible technique for characterizing LV regional systolic myocardial motion on a per-segment basis in healthy volunteers.